COBOL Programming / A Structured Approach Third Edition - Abel Peter (Prentice Hall, 1989)
A fresh approach to learning the COBOL language. Preface, Acknowledgements, The World of Computing, Fundamental COBOL, Logic and Control, Special Data Handling, File Organization Methods, Special Topics, Index.